The dynamic interaction of land use and transport in a highly fragmented city: the case of Cape Town, South Africa - Moyo, Hazvinei Tsitsi Tamuka (Department of Civil Engineering, 2020)
The need for more inclusive and integrated cities has resulted in a paradigm shift in the South African transport and land use policy environment where transport and land use planning are viewed as a continuum as opposed to isolated planning aspects. Issues such as residential segregation, social exclusion, spatial inefficiencies, inequality, residential informality, marginalisation of the low-income cohort continue to form part of the current planning discourse. While policy acknowledges the need to redress these issues, the urban spatial patterns in South African cities continue to trace the historical planning trajectory. Recently, congestion has become an issue in some of South Africa’s cities with Johannesburg and Cape Town appearing in the list of the top hundred most congested cities in the world. It is thus essential to understand how South African cities can address urban accessibility and mobility issues along with redressing apartheid spatial planning to attain sustainable cities that allow for inclusivity of all population groups. Like most South African cities, Cape Town is a relic of apartheid planning where the urban spatial patterns reinforce social exclusion among other issues. Urban and transport planning in Cape Town focuses on addressing issues of spatial inefficiencies, social exclusion, congestion due to rapid motorisation and the proliferation of informal settlements. It is against this backdrop that the central concern of this research is to understand urban dynamics linked to the spatiotemporal interaction of transport and land use in Cape Town to aid in the formulation of proactive urban policies. There is compelling evidence in the literature that dynamic integrated land use transport models provide an avenue through which the urban change process can be understood to aid in the development of adaptive land use and transport strategies. METRONAMICA, a dynamic land use transport model, is applied in this research to simulate and understand land use and transport change in Cape Town. A sequential stage-wise procedure was implemented to calibrate the model for the period 1995- 2005 and an independent validation was carried out from 2005 to 2010 to evaluate the model. Kappa statistic and its associated variants were applied to assess the ability of the land use model block to reproduce land use patterns while the EMME model and previous transport studies for Cape Town were used to evaluate the transport model. The results from the calibration and validation exercise show that the model can reproduce historical land use and transport patterns. The integration of the transport and land use model through accessibility improved the Kappa Simulation and Fuzzy Kappa Simulation. This showed that the model explained urban change better when land use and transport interacted compared to an independent land use model. This shows that accessibility can be employed in the Cape Town context to enhance the understanding of the urban change process. In addition to the Kappa statistics, the fractal dimension which measures the landscape complexity was used to assess the predictive accuracy of the model. The model performance revealed that the landscape patterns simulated by the model resemble observed land use patterns signifying a good calibration of the model. The calibrated land use transport model for the Cape Town Metropolitan region (CTMRLUT) was applied for policy scenarios. Three scenarios were simulated, specifically the business as usual (BAU), redressing social exclusion and the potential for in situ upgrading of informal settlements. The study found that intensive land use development along the Metro South East Integration Zone (MSEIZ) was linked to a reduction in commuting distances to economic activities which is in contrast to the BAU scenario. While these scenarios looked at the urban spatial patterns, the effect of land use patterns on congestion was also explored. The findings from the scenario simulations suggest that despite the reduction in distance to economic centres, the congestion condition in Cape Town will continue to deteriorate. Further, the findings indicate that interventions that only target land use developments are not sufficient to address congestion issues in Cape Town. Instead, to address the congestion problem in Cape Town, mixed land use and compact growth strategies need to be complemented with travel demand management strategies that target private car usage and intensive investment in transport infrastructure, especially rail, to facilitate the use of alternative modes. With regards to informal settlements, the study found that in situ upgrading could be a viable option to tackle some informal settlements. However, for proper inclusionary informal settlement policy, an approach that resonates with contextual realities would be more suitable to assess the viability of in situ upgrading based on the location of informal settlements relative to centres of economic activities. Additionally, the study revealed that instead of informal settlements locating as stand-alone settlements, some of them located adjacent to low-income housing which might be indicative of a growth in backyard shacks which is an existing housing trend in some lowincome suburbs in Cape Town. While this research has shown that integrating land use and transport in policy is potentially useful in solving urban issues, it has also revealed the value of urban modelling as a platform on which to assess the potential impacts of policies before their implementation. This is a strong case for the utilisation of decision support tools in land use and transport planning in contemporary South African cities.